Bombyx mori nucleopolyhedrovirus downregulates transcription factor BmFoxO to elevate virus infection. (March 2021) - Kang, Xiaoli; Wang, Yaping; Liang, Wenjuan; Tang, Xin; Zhang, Yan; Wang, Lingyan; Zhao, Ping; Lu, Zhongyan
Abstract: Forkhead-box O (FoxO) is the primary transcriptional effector of the insulin-like signaling pathway that enhances gluconeogenesis through transcriptional activation of PEPCK and G6Pase in mammals. We have previously demonstrated the involvement of phosphoenolpyruvate carboxykinase ( BmPEPCK-2 ) in antiviral immunity against the multiplication of Bombyx mori nuclearpolyhedrosisvirus (BmNPV) in silkworm. Therefore, we speculated that BmFoxO might suppress BmNPV by regulating the expression of PEPCK in silkworm. In the present study, we found that the expression of BmFoxO decreased after BmNPV infection in Bombyx mori ; this finding was consistent with BmPEPCK-2 expression. In addition, the expression of BmFoxO was altered, and it was found that reduced expression of BmFoxO ( dsBmFoxO ) downregulated the expression of BmPEPCK-2 and increased the viral fluorescence and content in silkworm embryonic cell line BmE cells, and vice versa. BmFoxO could upregulate the expression of BmPEPCK-2 by binding to the BmPEPCK-2 promoter. Moreover, overexpression of BmFoxO significantly increased the expression of autophagy genes ATG6 /7/8 after infection with BmNPV, consistent with BmPEPCK-2 . These results indicate that BmNPV downregulates transcription factor BmFoxO to elevate virus infection, and BmFoxO overexpression upregulates BmPEPCK-2 expression and enhances silkworm antiviral resistance. Highlights: BmNPV induces a continuous reduced expression of BmFoxO. Overexpression of BmFoxO inhibited BmNPV multiplication. BmFoxO regulates transcription of BmPEPCK-2 by binding to its Fork head element. Overexpression of BmFoxO may increase autophagy by regulating the expression of BmPEPCK-2.